Indonesian Presidential Election 2019 – Jokowi’s Chances in Post-Kalla South Sulawesi - Dinarto, Dedi (2019)
Jusuf Kalla’s elusive support for Joko Widodo (Jokowi) along with strong backing from Islamist groups for Prabowo Subianto does not bode well for Jokowi’s chances in South Sulawesi. Growing discontent towards old established elites as well as identity politics looks set to shape the state of affairs in the coming presidential election.